Surveying and mapping strategy for supporting the emerging land market in Albania - Jazoj, Ahmet; Lamani, Spiro; Lira, Leart; University of Wisconsin--Madison. Land Tenure Center.; Albania. Immovable Property Registration and Market Action Plan (Project). Project Management Unit. (Land Tenure Center, University of Wisconsin-Madison, 1997)
Moving toward a market-oriented economy involves the development of various types of markets. One of the first steps of the transition in Albania has been the property privatization process, that is, the transformation of state property into private holdings. A critical issue encountered in this activity is the setting up of a land registration system. The implementation of an Immovable Property Registration System (IPRS) has now begun in Albania as part of the Land Market Action Plan, which is supported by technical and economic assistance from the U.S. Agency for International Development (USAID) and the European Union PHARE program. This paper describes the strategy and procedures that are followed in Albania for the production of cadastral maps and the importance of these maps for the IPRS, which will serve the future land market. The procedure for producing base cadastral maps for registration purposes is to use existing maps, choose appropriate scales, and transform these into one, unique coordinate system. The strategy for surveying and mapping is to begin with the existing level of technology and gradually introduce new techniques.
iv, 15 p.
Keywords: Cartography Albania; Cadastres Albania; Land use Albania; Land administration Albania